Toxicidade de manipueira sobre Meloidogyne spp. - Camara, Guilherme de Resende (2015)
The cassava is a liquid extracted from the cassava (Manihot esculenta L.) during the manufacturing process of the flour and contains a toxic glycoside called linamarin, which originates hydrocyanic acid (HCN), substances responsible for toxic effects on p